The Functional Role of Individual Alpha-Based Frontal Asymmetry in the Processing of Fearful Faces - Liu, Lei; Zhou, Renlai (Frontiers in Psychology, 2020)
The ability to identifying fearful faces quickly is important for individuals activating the defense mechanism to deal with potential emergencies. This study examined the relation of an individual’s frontal electroencephalography (EEG) alpha asymmetry to the processing of congruent and incongruent fearful faces for female participants by using event-related potentials (ERP). Behavioral results showed that individuals with more left frontal EEG alpha asymmetry had shorter response times than individuals with more right frontal EEG alpha asymmetry during the cue-target task. ERP results showed that: For individuals with more left frontal EEG alpha asymmetry, larger N1 reflected that they rapidly processed the emotional faces in the early stage and larger P3 reacted that they directed more attentional and motivational resources to evaluate the emotional faces in the late stage. For individuals with more right frontal EEG alpha asymmetry, enhanced N2 indicated that they had more conflicting for incongruent fearful faces in the late stage. The present findings suggested that frontal EEG alpha asymmetry at resting condition can reflect individual differences in the processing of congruent and incongruent fearful faces.